Modifying the triple helix model of innovation: a lesson learned from Cimahi Techno Park in Indonesia. (2nd September 2020) - Kusharsanto, Zulfika Satria
Collaborations with triple helix model between academia, government, and business have been an eminent approach to generate knowledge economy especially in regional development. Those practices are widely implemented in a science park, the centre where collaborations occur to commercialise research. Nonetheless, many countries have apparently not experienced similar result as suggested by the triple helix model. This is thought-provoking because the triple helix model in science park is globally encouraged regardless. With the case of Cimahi Techno Park in Indonesia, this study observes why the collaborations in science park can be maintained despite the existence of deviances. This study reveals that there are some compromises and modifications in the triple helix model to adjust innovation system with local conditions, such as involving universities for entrepreneurial consultation instead of research and altering science park as 'the catalyst' of local economic development instead of as the 'hybrid organisation'.